Dual Constitutions and Concurrence of Constitutional Powers in Ethiopia: Who Has the Mandate to Determine Particulars by Law? - Afesha, Nigussie (Bahir Dar University Journal of Law, 2022)
Federations vary in the crafting of their constitutions. These variationsrange from those federations whose constitutional distribution of power istoo comprehensive, including details normally articulated in ordinarylegislation, to those federations whose constitutions endeavor to demonstratethe major tasks of government in a holistic manner. In those federationswhich follow the latter trend, only the major issues are stated in theirconstitutions. The Ethiopian practice resembles the second model. Afterincorporating major issues explicitly, the FDRE Constitution leaves thedetails to be determined by ordinary legislation. The same arrangement isobserved in regional states‟ constitutions. The issue therefore is who has themandate to determine the details through legislation: the federal or regionalgovernments? This article explores how the Constitution provides in whatmanner the particulars shall be determined by law and attempt to indicatewho has the mandate to do that.